Determinants of intention to continue usage of online shopping under a pandemic: COVID-19 - Hamood Mohammed Al-Hattami (Cogent Business & Management, 2021)
Although numerous reports predict huge growth potential for online shopping under COVID-19 pandemic, many do not know about determinants of user intention to continue using online shopping under such a pandemic. Given that how to motivate continuousness and retain consumers under a pandemic is critical to the online retailers and relevant stakeholders' success, research on the determinants of intention to continuance using online shopping has attracted widespread attentiveness. The determinants of intention to continue using online shopping under COVID-19 pandemic, especially in India, have not yet been researched. Therefore, this study proposes a model combining the expectation-confirmation model (ECM) with task-technology fit (TTF) model and the trust factor to examine intention to continue using online shopping under COVID-19. Based on data gathered from 222 online participants during the period of social distancing due to COVID-19, the findings revealed that perceived TTF is much significant factor; satisfaction, perceived usefulness, and trust have positive impacts on consumers' intention to continue usage of online shopping under COVID-19. Additionally, confirmation directly affects satisfaction, perceived usefulness, and indirectly affects consumers' intention to continuance usage. The study's findings provide online retailers and related stakeholders with significant managerial implications.
Keywords: 650; Online shopping; continuous usage; ECM; TTF; trust; pandemic; COVID-19